Comparative analysis of touchscreen inceptors and traditional sidesticks on flight decks: flight performance, visual behaviours and situation awareness - Wang, Yifan; Korek, Wojciech Tomasz; Blundell, James; Li, Wen-Chin (Taylor & Francis, 2026)
The concept of touchscreen primary control device is a novel approach of touchcreen implentation. The objective of this study is to investigate differences in flight performance and attention allocation between a touchscreen inceptor and a traditional sidestick. Twenty-one participants flew four simulated instrument landing system (ILS) approaches - with the touchscreen inceptor or traditional sidestick - during flight scenarios where an aircraft attitude disturbance was either present or absent. Results demonstrated that participant performance scores were worse with the touchscreen inceptor compared to the sidestick during attitude disturbance scenarios. Interestingly, participants exhibited reduced attention to external visual cues with the touchscreen inceptor compared to the sidestick. In addition, use of the touchscreen inceptor resulted in lower performance and lower self-reported situation awareness. Overall, the touchscreen inceptor demonstrated poorer performance compared to the traditional sidestick, highlighting limitations in its current design that warrant cautious consideration and further investigation.
Keywords: 5201 Applied and Developmental Psychology; 4201 Allied Health and Rehabilitation Science; 42 Health Sciences; 4207 Sports Science and Exercise; 52 Psychology; Flight deck design; human-computer interactions; situation awareness; touchscreen inceptor; visual behaviours; Human Factors